Operation Dunkirk - Lyon, Nick, 1970-; Cole, Tyler; Meredith, Ifan; Asylum (Firm) ([Burbank, California] : The Asylum, 2017)
A band of soldiers left behind in the last hours of the evacuation of Dunkirk must battle their way through dangerous Nazi territory if they ever hope to return home again.
Widescreen.
Tyler Cole, Ifan Meredith, Kimberly Hews, Michael Wouters, Darren Hill, Kyle Hotz, Conner Kelley, Gerard Pauwels, Paul Nicely, Eddie Curry, Christopher W.D. Howe, Charles Adams, Jerry L. Beasley.
DVD.
Closed-captioned.
105746
Keywords: Dunkirk, Battle of, Dunkerque, France, 1940 -- Drama; World War, 1939-1945 -- Campaigns -- France -- Drama; Military campaigns; France; Fiction films; Feature films; War films; Action and adventure films; Video recordings for the hearing impaired